Brief Analysis of the Dispute Resolution Methods through Mediation in Romania - IGNAT, Claudiu (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v10.1(47).07, 2020)
Mediation is an alternative way of resolving conflicts and in particular disputes that may otherwise reach a judiciary settlement. This procedure is a voluntary choice for the warring parties, but may be a compulsory procedure, when mediation is the only way to resolve disputes stipulated through a compromissory clause in the contract bet of the parties they are in dispute. Even though mediation is a non-contentious procedure, it has a set of rules and principles that govern this procedure, guaranteeing the respect of the rights of all parties in the dispute over mediation.